Electron trapping and acceleration by the plasma wakefield of a self-modulating proton beam - Lotov, K. (2014)
It is shown that co-linear injection of electrons or positrons into the wakefield of the self-modulating particle beam is possible and ensures high energy gain. The witness beam must co-propagate with the tail part of the driver, since the plasma wave phase velocity there can exceed the light velocity, which is necessary for efficient acceleration. If the witness beam is many wakefield periods long, then the trapped charge is limited by beam loading effects. The initial trapping is better for positrons, but at the acceleration stage a considerable fraction of positrons is lost from the wave. For efficient trapping of electrons, the plasma boundary must be sharp, with the density transition region shorter than several centimeters. Positrons are not susceptible to the initial plasma density gradient.